Income Inequality in Israel: A Distinctive Evolution - Momi Dahan (Center for Economic Studies and ifo Institute (CESifo), 2017)
The level of disposable income inequality in Israel has increased noticeably since the mid-1980s and today it is above most developed countries. In contrast, market income inequality, which hit a record level in 2002, has reversed its course since then and has shown a sharp decline in subsequent years, and it is now below the OECD average. This paper offers tentative explanations for the inverted U-shape evolution of market income inequality in Israel in the last 25 years, which is distinctive in view of most developed countries' experience. In addition, this article addresses the unique combination of income inequality in Israel which has one of the highest levels of disposable income inequality but is ranked below the OECD average measure of market income inequality.
Keywords: C00; 330; income inequality; redistribution policy; labor market institutions; SBTC